Paediatric appendiceal ultrasound: a survey of Australasian sonographers' opinions on examination performance and sonographic criteria. Issue 4 (28th October 2018) - Reddan, Tristan; Corness, Jonathan; Harden, Fiona; Mengersen, Kerrie
Abstract: Introduction: The objectives of this study were to identify knowledge gaps and/or perceived limitations in the performance of paediatric appendiceal ultrasound by Australasian sonographers. We hypothesised that: sonographers' confidence in visualising the appendix in children was poor, particularly outside predominantly paediatric practice; workplace support for prolonging examinations to improve visualisation was limited; and the sonographic criteria applied in diagnosis did not reflect contemporary literature. Methods: A cross‐sectional survey of Australasian sonographers regarding paediatric appendicitis was conducted using a mixed methods approach (quantitative and qualitative data). Text responses were analysed for key themes, and quantitative data analysed using chi‐square, Mann–Whitney U and Wilcoxon signed‐rank tests. Results: Of the 124 respondents, 27 (21.8%) reported a visualisation rate of less than 10%. Workplace support for extending examination time was significantly related to a higher appendix visualisation rate ( χ 2 (2) = 16.839, P < 0.001). Text responses reported frustration locating the appendix and a desire for more time and practice to improve visualisation. Sonographers suggested a significantly lower maximum diameter cut‐off in a 5‐year‐old compared to a 13‐year‐old ( Z = −6.07, P < 0.001), and considered the presence of inflamed peri‐appendiceal mesentery as the most useful sonographic criterion in diagnosing acute appendicitis. Conclusions: Respondents had a low opinion of their ability to confidently identify the appendix. Confidence was greater in those centres where extending scanning time was encouraged. Application of echogenic mesentery as the most significant secondary sonographic criterion is supported by recent studies. Opinions of diameter cut‐offs varied, indicating potential for improved awareness of recent research. Abstract : The objectives of this study were to identify knowledge gaps and/or perceived limitations in the performance of paediatric appendiceal ultrasound by Australasian sonographers. A cross‐sectional survey of Australasian sonographers regarding paediatric appendicitis was conducted using mixed methods (quantitative and qualitative data). Respondents had a low opinion of their ability to confidently identify the appendix, though confidence was greater in those centres where extending scanning time was encouraged.